Small scale and micro featured functional prototypes generated by laser sintering of polyetheretherketone - Rechtenwald, T.; Krauß, H.J.; Pohle, D.; Schmidt, Michael (Proceedings of the XII. Conference on Micromachining and Microfabrication Process Technology, San Jose (USA), 22.-24., 2007)
Functional prototypes produced via laser sintering already address the sub millimeter region with resolutions in the low micrometer range. The manufacturing process is very suitable for small scale, micro featured functional polymer parts because of its ability to generate complex and fine shaped geometries including undercuts and pores. The parts are built up layer by layer from three-dimensional data generated by CAD programs or by micro computer tomography as a copy of already existing parts. Up to now this field is dominated by polyamide, a semi-crystalline polymer. This thermoplastic material covers a wide range of applications but requirements concerning a high temperature resistance above 200 °C and tensile strengths above 50 N/mm 2 are not fulfilled despite glass fillings. A change in the sintering material can solve this issue. Investigations show that polyetheretherketone (PEEK) which is a high performance polymer with a melting temperature of 346°C can be used for laser sintering. Manufacturing small sized and micro featured parts with enhanced temperature and mechanical properties is possible using an adapted system technology. For minimum vertical outer features a value of about 250 μm was found, expanded outer features like walls show a width of 650 μm. A first low boundary for hole-diameters in the feeding 3D-data set was found. As a basic boundary for minimum geometrical features a core roughness average of about 23.3 μm could be measured.
LFT Import::2019-08-05 (1426)
Keywords: Functional prototypes; Laser sintering; PEEK; Polyetheretherketone; Polymer; Rapid prototyping; SLS